Educational program emergency planning. - Curtis T (Radiologic Technology)
BACKGROUND: Tragic university shootings have prompted administrators of higher education institutions to re-evaluate their emergency preparedness plans and take appropriate measures for preventing and responding to emergencies. OBJECTIVE: To review the literature and identify key components needed to prevent shootings at higher education institutions in the United States, and in particular, institutions housing radiologic science programs. METHODS: Twenty-eight emergency preparedness plans were retrieved electronically and reviewed from a convenience sample of accredited radiologic science programs provided by the Joint Review Committee on Education in Radiologic Technology Web site. RESULTS: The review of the 28 emergency preparedness plans confirmed that most colleges are prepared for basic emergencies, but lack the key components needed to successfully address mass-casualty events. Only 5 (18%) of the 28 institutions addressed policies concerning school shootings.